Nandi mandapa in front of the Harshnath Temple - Temples of India Project Team (Jio Institute, 2024)
A white stone image of Nandi, Shiva’s bull, placed over the Nandimandapa facing the Harshnath Temple. The image could be a later replacement of the original image. The Verse-12 of the Harshnath stone inscription records ‘Resembling (in height) the peak of Meru, it is pleasant on account of an excellent arched doorway (torana-dvara), and well-carved bull (Nandi), and is full of manifold objects of enjoyment’. The mentioned image of Nandi, whether original or a later replacement, presents a visual correspondence to the epigraphical description of the temple complex.